Pengembangan Website Informasi Sekolah di SMP Negeri 2 Kalimanah, Purbalingga - Yogiek Indra Kurniawan; Nur Chasanah; Nofiyati Nofiyati (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2020)
Sekolah Menengah Pertama Negeri (SMP N) 2 Kalimanah is a secondary school located in the Kalimanah area, Purbalingga, Central Java. Based on observations and interviews that have been conducted, there are problems at the school, namely regarding the promotion and dissemination of information outside the school which is still lacking because at this time it is only focused on posters and wall magazines. The solution that can be given at SMP N 2 Kalimanah is to create a school information website that specifically displays information for SMP N 2 Kalimanah. With the website, the school can connect more easily with parties outside the school because the website can be accessed by everyone anywhere and anytime as long as it is connected to an internet connection. The service activities are divided into several stages, namely need assessment, application implementation, presentation and website training to teachers, as well as simulation and testing. The result of this activity is a school information website at SMP N 2 Kalimanah that can display news, photos, and activities in the school environment to the wider community. In addition, based on the tests that have been carried out, 95% of respondents stated that the school information website had succeeded in solving the problems of promotion and news delivery at SMP N 2 Kalimanah.